Concise Review: Animal Substance-Free Human Embryonic Stem Cells Aiming at Clinical Applications. (8th October 2014) - Hovatta, Outi; Rodin, Sergey; Antonsson, Liselotte; Tryggvason, Karl
Abstract : This review examines clinical applications of animal substance-free human embryonic stem cells. Following studies on factors regulating pluripotency and differentiation, there are now techniques to establish and effectively expand these cells in animal substance-free conditions, even from single cells biopsied from eight-cell stage embryos in chemically defined feeder-free cultures. Early clinical trials are ongoing. Abstract: Human embryonic stem cells have been considered the gold standard as a cell source for regenerative medicine since they were first cultured in 1998. They are pluripotent and can form principally all the cells types in the body. They are obtained from supernumerary human in vitro fertilization embryos that cannot be used for infertility treatment. Following studies on factors regulating pluripotency and differentiation, we now have techniques to establish and effectively expand these cells in animal substance-free conditions, even from single cells biopsied from eight-cell stage embryos in chemically defined feeder-free cultures. The genetic stability and absence of tumorigenic mutations can be determined. There are satisfactory animal tests for functionality and safety. The first clinical trials are ongoing for two indications: age-related macular degeneration and spinal cord injury.